Cepharanthine Hydrochloride Improves Cisplatin Chemotherapy and Enhances Immunity by Regulating Intestinal Microbes in Mice - Zhou, Pengjun; Li, Ziyao; Xu, Dandan; Wang, Ying; Bai, Qi; Feng, Yue; Su, Guifeng; Chen, Pengxiao; Wang, Yao; Liu, Huizhong; Wang, Xiaogang; Zhang, Rong; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Chemotherapy is one of the major treatment strategies for esophageal squamous cell carcinoma (ESCC). Unfortunately, most chemotherapeutic drugs have significant impacts on the intestinal microbiome, resulting in side effects and reduced efficiency. Therefore, new strategies capable of overcoming these disadvantages of current chemotherapies are in urgent need. The natural product, Cepharanthine hydrochloride (CEH), is known for its anticancer and immunoregulatory properties. By sequencing the V4 region of 16S rDNA, we characterized the microflora of tumor-bearing mice treated with different chemotherapy strategies, including with CEH. We found that CEH improved the therapeutic effect of CDDP by manipulating the gut microbiota. Through metagenomic analyses of the microbial community, we identified a severe compositional and functional imbalance in the gut microbial community after CDDP treatment. However, CEH improved the effect of chemotherapy and ameliorated CDDP treatment-induced imbalance in the intestinal flora. Mechanically, CEH activated TLR4 and MYD88 innate immune signaling, which is advantageous for the activation of the host’s innate immunity to exert a balanced intestinal environment as well as to trigger a better chemotherapeutic response to esophageal cancer. In addition, TNFR death receptors were activated to induce apoptosis. In summary, our findings suggest that chemotherapy of CDDP combined with CEH increased the effect of chemotherapy and reduced the side effects on the microflora and intestinal mucosal immunity. We believe that these findings provide a theoretical basis for new clinical treatment strategies.